Antioxidant and Sunscreen Activities of Ethanol Extract Body Lotion Preparation of Dewandaru Leaves (Eugenia Uniflora L.) - Anwar, Khoirul; Yumni, Gharsina Ghaisani; Putri, Aulia Septiani; Britama, Melani Putri (Jurnal Ilmiah Sains, 2025)
Dewandaru (Eugenia uniflora L.) is one of the plants that has antioxidant properties and activity as a sunscreen, so to facilitate its use it must be formulated in the form of body lotion. This study aims to test the antioxidant and sunscreen activity of a body lotion preparation from dewandaru leaf extract. Ethanol extract of dewandaru leaves is obtained by maceration using 96% ethanol. The ethanol extract of dewadaru leaves was identified as an active compound using phytochemical screening and FTIR. The body lotion formulation uses an extract with a concentration of 5% (F1); 10% (F2) and 15% (F3). Body lotion was tested for antioxidant and sunscreen activity using the ABTS method and the Mansur equation. The results of the absorbance data were analyzed using linear regression to obtain the IC₅₀ value and SPF value. The results of phytochemical screening showed that dewandaru leaf extract contained phenolic compounds and flavonoids. It was proven by the FTIR test results that the ethanol extract of dewandaru leaves contains flavonoid compounds such as dihydroflavonol which have the functional groups OH, aliphatic CH, C=O and C–O. Evaluation of the physical characteristics of body lotion preparations, all formulas meet the requirements. Dewandaru leaf ethanol extract body lotion has strong antioxidant activity in all formulas and the best antioxidant activity results were obtained at F3 with an IC50 value of 59.85 ppm. Dewandaru leaf ethanol extract body lotion has the potential as a sunscreen with an SPF value of F1, namely 7.5675 in the extra protection category, F2, namely 16.1866 in the ultra protection category, and F3, namely 17.003 in the ultra protection category. So based on the results above, the greater the concentration, the stronger the antioxidant activity and sunscreen activity obtained. Keywords: Antioxidants; body lotion; dewandaru leaves; sunscreen